Facilitating K-12 Teachers in Creating Apps by Visual Programming and Project-based Learning - Chiu, Chiung-Fang (International Journal of Emerging Technologies in Learning (iJET), 2020)
The use of apps in education has become popular in recent years with the development of technology. How to prepare K-12 teachers in creating apps for students learning is worth our attention. This paper presents how to ap-ply visual programming and project-based learning to facilitate K-12 teachers in creating apps. Seven K-12 teachers with less computer background partic-ipated in this study. Data source including (1) K-12 teachers’ project codes, (2) K-12 teachers’ questionnaire, (3) K-12 teachers’ interviews, and (4) ques-tionnaire giving to K-12 students were collected and analyzed. The results reveal that K-12 teachers applied many programming concepts in the coding implementation in these projects. Most students gave positive feedback to these K-12 teachers’ app projects. Furthermore, K-12 teachers were also very positive toward the creation of apps by visual programming and project implementation, which was reflected through K-12 teachers’ questionnaire surveys and interview results. The above findings provide a practicable ap-proach for future teaching to K-12 teachers or novice programmers on app programming.